FENOMENA UNDERPRICING PADA PERUSAHAAN YANG GO PUBLIC DI INDONESIA - Purwanto .; Sri Wahyu Agustiningsih; Salman Faris Insani; Budi Wahyono (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2014)
This research trytoanalyzethe factors thatinfluence the occurrence ofunderpricingin companies thatgopublic. This study uses a more variable varies the financial and non-financial variables contained in the prospectus which is composed of the reputation of the underwriter, auditor reputation, firm size, financial leverage, return on assets (ROA) and return on equity (ROE). According to the results of previous studies, these variables generally tend to show a significant effect on underpricing in companies that go public. This research is ekspost facto (causal comparative). Sample selection method used was purposive sampling and sample used was 132 sample companies doing an Initial Public Offering on the Indonesia Stock Exchange in the period 2002-2012. This study uses regression testing models. Regression analysis showed that nlytheunderwriterreputationsignificantly influenceunderpricing